INFLUENCE OF THE LEVEL OF EDUCATION ON PROGRESSION OF WOMEN TO LEADERSHIP POSITIONS - A., M.A, OSIJE, Majina; M. O., PhD, Dr. YAMBO John (IJRDO - Journal of Applied Management Science, 2016)
The study was conducted in Mabera division, Kuria west, Migori County to investigate the factorsthat influence to progression of women to leadership positions. The 1995 Beijing Platform forAction, emphasized that ‘women’s equal participation in decision making is not only a demandfor justice or democracy, but can also be seen as a necessary condition for women’s interests to betaken into account. The objective of the article was to determine the influence of the level ofeducation on progression of women to leadership position in Mabera Division, Migori County.The study was guided by The Classical Liberal Theory of Equity of Opportunity (Classicalliberalism or libertarianism) that holds that women and men are self-owners capable of acquiringproperty rights over things. The study used descriptive survey that targeted a population of 9523women from different households within the division. The Krejcie, Robert V., Morgan table wasused to calculate the sample population size and that gave the researcher a sample size of 373women interviewed. Questionnaires were used as research instruments which the respondentsfilled during the survey. Data collected from the field was coded and ultimately analyzed byperforming several descriptive statistical computations such as frequency distribution tables andmeasures of central tendencies. Frequency tables were used to present data. The study revealedthat majority of women interviewed 48.4% had primary level of education and only 35.8%managed to reach secondary level. Generally, this implies low levels of education in the area asfar as women education is concerned. The researcher concluded that there is need to educate girlchild in the division so that they can participate in leadership. The researcher recommended thatLeadership Forums & Social Networking gatherings should provide opportunities for women toexchange experience and wisdom with other women in equivalent positions